3487 Trust in Research Among Older Adults. (27th March 2019) - Striley, Catherine Woodstock; Lloyd, Shawnta; Varma, Deepthi; Vaddiparti, Krishna; Cottler, Linda B.
Abstract : OBJECTIVES/SPECIFIC AIMS: Adults, 60 years of age and older, are in high demand for enrollment in many types of health research. Here we aimed to examine baseline, 60-day and 120-day follow-up trust in research and researchers of Floridians 60 years of age and older engaged in University of Florida's HealthStreet community engagement initiative. METHODS/STUDY POPULATION: HealthStreet Community Health Workers (CHWs) assess health needs and trust in research of community members and screen for dementia, before providing medical and social services referrals and linkages to opportunities to participate in relevant health research at UF. In addition, participants are followed up at 60 and 120 days. RESULTS/ANTICIPATED RESULTS: Among the 2, 193 older adults assessed by CHWs, 62.6% were female, 46.8% were African American, and 6.1% Hispanic/Latino. At baseline, 28.3% reported ever being in a research study; 7.7% reported not being interested in participating in research. Trust in research and researchers was high at baseline [scored from 1 to 10 where 10 was high; mean of 7.4 each for trust in research (SD=2.0) and trust in researchers (SD=2.1)] and high at both follow-ups [60 days 7.8 (SD=2.1) and 7.7 (SD=2) for trust in research and researchers respectively; 120 days 8.0 for both (SD=1.9 and 1.8 respectively)]. DISCUSSION/SIGNIFICANCE OF IMPACT: Individuals who are 60 and older have high trust in research and researchers when approached and high interest in research. Their trust continues through work with HealthStreet CHWs. Community engagement is an important part of the pipeline for recruitment of older adults for research.